Village Accounting Reconstruction Methodology Based on the Kingdom of God - Ivana Nina Esterlin Barus (Yayasan Rumah Peneleh, 2021)
his article aims to develop a research methodology in the field of village accounting that is religious and spiritual in nature to redirect village accounting practice to its holiness and religiousity simultaneously. The construction of a refined village accounting methodology was carried out through a study of the financial management of the Kingdom of God according to the Church Reform Leader, Martin Luther and historical analysis on the practice of village accounting. The result is a village accounting research methodology with religious and spiritual principles of the Kingdom of God. New Life as a methodology that will be constructed to restore the purity of village accounting, clearly rejects the impure, as a powerful way to improve the financial management system for a better governance. Village accounting based on the kingdom of God is based on the loyal principle: to organize, to receive, and to faithfully sow. In practice, this principle will be able to realize the ideals of the Indonesian people to break free from the confine of capitalism and neoliberalism.